A natureza como ensino-aprendizagem: oportunidades para a infância - Paula, Maiara Gabriela Graeff de (2020)
This article, required for the conclusion of the Pedagogy Course, from the University of Passo Fundo, presents a study related to nature as part of the teaching-learning process and as a source of opportunities for childhood. We sought to understand the repercussions of contact with the environment, when used as educational space, for an investigative development of children in early childhood education. Still, points considerations about a healthier, more playful and effective childhood, about the planning process elaborated by the teacher, which must be done in order to make different experiences possible for individuals, who go to the meeting the real objectives of this teaching modality. This work has a bibliographic nature and was elaboratet before theories and research, addressing different theorists, such as: Louv (2016), Meirelles et al. (2017), Gazola and Mascioli (2019), and Hungary (2016). Thus, this investigation allowed different views and appropriations to the study done, taking into account some reflections already raised, in academic environments, around this thematic. Thus, it was emphasized that it is essential to think about early childhood education and connect it to the environment that most educates and teaches, providing a more positive and pleasant childhood in this teaching stage.